Yq microdeletions and their current status in relation to Indian and Global scenario associated to male infertility: A mini appraisal - Nidhi P Shah; Parth S Shah; Rutvik J Raval; Rahul Yadav; Sandip C Shah; Mandava V Rao (Eastern Journal of Medical Sciences, 2021)
Background: Y chromosome microdeletions provide a pivotal role in the control of spermatogenesis. These are located on the q arm of it, specifically, the azoospermia factor (AZF) region, hence named as Yq microdeletions. The mutations in this region are related to testicular pathologies such as azoospermia, oligozoospermia, and other semen categories. Objectives: This study was undertaken to review these microdeletions, screening, and their correlation to semen categories in relation to the Indian and Global populations in context to male infertility, future strategies, and its implications. Methodology: These deletions are screened using sequence-tagged sites (STS) of the European Academy of Andrology (EAAs) and Non-EAAs with polymerase chain reaction technology. The data included were Indian and Global studies obtained from research articles, abstracts, and reviews (75) indexed in Google Scholar, PubMed, and Scopus. Results: A number of total 45,562 Y chromosomes were analyzed. In India, this frequency contributes to 8.33% (453/5435) against the average frequency of 6.96% (3170/ 45562) worldwide. Globally, this frequency was higher (9.1%) in the North American continent. Among all types of deletions, AZFc deletions are higher followed by b, a, b+c, and others as well as are related to azoospermia than oligospermia and other semen cases/categories globally including India. In India, the data on partial deletions are scanty. Further, cases with AZFc are better suitable for assisted reproductive technologies after counseling. Conclusion: Evaluation of correct deletion type to a specific testis pathologic phenotype is suggested for sperm retrieval to correct the male partner. This study is hence better suitable for azoospermia with AZFc deletion around the Global and Indian scenario in association with male infertility. Future strategies are thus called for successful treatment of a specific microdeletion clinically in the male.